Planning hospital medical technology management. - David, Y. (IEEE Engineering in medicine and biology magazine)
The appropriate deployment of technology contributes to the improvement in the quality of healthcare delivered, the containment of cost, and to increased access to services offered by the healthcare system. Over the past one-hundred years, the dependence of the healthcare system on medical technology for the delivery of its services has continuously grown. In this system, the technology facilitates the delivery of the "human touch." Medical technology enables practitioners to collaboratively intervene together with other caregivers to treat patients in a cost-effective and efficient manner. Technology also enables integration and systems management in a way that contributes to improvements in the level of health indicators. Hospital and clinical administrators are faced with the expectation for return on investment that meets accounting guidelines and financial pressures. This article describes the emerging process for managing medical technology in the hospital and the role that clinical engineers are fulfilling.